Pengaruh Kualitas Pelayanan dan Promosi terhadap Kepuasan Pelanggan pada Alfamart di Depok - Junia Rahmawatiara; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the impact of service quality and promotion on customer satisfaction at Alfamart in Depok City. The research uses a quantitative approach with data collected through questionnaires filled out by 100 respondents. Data analysis techniques include data quality tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests using IBM SPSS version 25. The results of the T-test indicate that service quality (X1) has a significant impact on customer satisfaction (Y), with a t-value of 2.851 > 1.661 and a significance value of 0.005 < 0.05. Meanwhile, promotion (X2) does not show a significant effect on customer satisfaction (Y), with a t-value of 6.938 > 1.661 and a significance value of 0.000 < 0.05. The F-test shows that, simultaneously, service quality and promotion have a significant effect on customer satisfaction (Y), with an F-value of 84.772 > F-table 3.090 and a significance value of 0.000 < 0.05. Based on the coefficient of determination test, it is found that 63.6% of customer satisfaction is influenced by service quality and promotion, while the remaining percentage is influenced by other factors.